Pembagian Daya pada Kendaraan Listrik Berbasis Sistem Hybrid Baterai dan Superkapasitor dengan Fuzzy Logic Controller - Andika, Yudi; Annisa, Aulia; Sa’diyah, Aminatus; Widodo, Hendro (Journal of Applied Smart Electrical Network and Systems, 2025)
This research discusses the application of Energy Management System on hybrid batteries and superkapasitors for power distribution as an effort to distribute the load on electric vehicles. The purpose of the research conducted is to determine whether the proposed Fuzzy Logic Controller-based control system can operate well as an effort to distribute power for the needs of operating electric vehicles. The driving cycle that will be used in the study is the Urban Dynamometer Driving Schedule (UDDS) cycle to determine the effect of power sharing on hybrid batteries and superkapasitors in the UDDS driving cycle. Testing was carried out under 2 different conditions, namely when the SOC condition of the battery and superkapasitor was 85% and when the SOC of the battery was 20% while the SOC of the superkapasitor was 85%. From the test, it was obtained that the proposed hybrid battery and superkapasitor system based on the Fuzzy Logic Controller was able to operate well under the specified conditions. Both energy storage devices were able to share power by maintaining the battery and superkapasitor SOC not exceeding the specified operating limits. This condition allows electric vehicles to be operated for a fairly long period of time.